THE STRATEGIC POLICY OF CITY GOVERNMENT IN DEVELOPMENT PLANNING FOR TOURISM IN PALANGKA RAYA CITY - Rendro Rismae Riady (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
This research aims to identify the level of readiness of the 6A components in destinations including: attractions, amenities, accessibility, availability of tourist packages (available packages), tourist activities (activities) and services, as well as public facilities (ancillary services) to produce The Strategic Policy Of City Government In Development Planning For Tourism In Palangka Raya City requires cooperation between the Government and the community, both in the form of developing a tourism-aware community and direct community involvement as investors in the tourism sector. Arrangement and revitalization of areas in the City of Palangka Raya by taking into account the social conditions and cultural character of the community, Arrangement and development of accessibility and public space facilities in the area. Development of creative spaces to gather creative people in the City of Palangka Raya and the policies are stated in the Regional Regulation of Palangka Raya City Number 11 of 2017 concerning the Master Plan for Tourism Development of Palangka Raya City 2017 – 2028.